2022
DOI: 10.1038/s41598-022-12126-3
|View full text |Cite
|
Sign up to set email alerts
|

Insights about the common generative rule underlying an information foraging task can be facilitated via collective search

Abstract: Social learning is beneficial for efficient information search in unfamiliar environments (“within-task” learning). In the real world, however, possible search spaces are often so large that decision makers are incapable of covering all options, even if they pool their information collectively. One strategy to handle such overload is developing generalizable knowledge that extends to multiple related environments (“across-task” learning). However, it is unknown whether and how social information may facilitate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
3
12
0
Order By: Relevance
“…We suggest the superior performance of groups relative to individuals and agents to be contingent on dialogical meta-cognition (Bang et al, 2014;Frith, 2012;Heyes, Bang, Shea, Frith, & Fleming, 2020;Naito et al, 2022;Shea et al, 2014), and its implications for the nature of participants' resulting problem representations, which, we claim, are more flexible and generalizable. Individuals solving the alien task on their own might be inclined to represent distinctive alien features mainly as visual traits (Smith & Sloman, 1994).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…We suggest the superior performance of groups relative to individuals and agents to be contingent on dialogical meta-cognition (Bang et al, 2014;Frith, 2012;Heyes, Bang, Shea, Frith, & Fleming, 2020;Naito et al, 2022;Shea et al, 2014), and its implications for the nature of participants' resulting problem representations, which, we claim, are more flexible and generalizable. Individuals solving the alien task on their own might be inclined to represent distinctive alien features mainly as visual traits (Smith & Sloman, 1994).…”
Section: Discussionmentioning
confidence: 80%
“…What are the mechanisms driving these effects? We suggest that the critical element lies in the dialogical integration of group members’ varied experiences giving rise to more abstract category representations (in this case, rule‐induction, R. Fusaroli et al., 2014; Naito et al., 2022; Olsen & Tylén, 2023; Toader & Kessler, 2018). And these appear to be particularly critical when encountering tasks of increasing complexity (Almaatouq et al., 2021).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A recent study [33] focused on similar situations and investigated whether and how knowledge of the old environment could be generalized to new environments in terms of an information search by social interactions. This study demonstrated that, through computational analyses of participants' behaviors in a multi-armed bandit task, paired participants performed a more efficient information search than solo participants.…”
Section: Fig 1 Hypothetical Examples Of the Wisdom Of Crowds By A Maj...mentioning
confidence: 99%
“…A recent study [ 33 ] focused on similar situations, investigating whether and how knowledge of the old environment could be generalized to new environments in terms of an information search through social interactions. This study demonstrated that, through computational analyses of participants’ behaviors in a multi-armed bandit task, paired participants performed a more efficient information search than solo participants.…”
Section: Introductionmentioning
confidence: 99%